Union of the Comoros : Action Plan for Implementation of the 2010-2014; Poverty Reduction and Growth Strategy. (IMF Staff Country Reports; Country Report ;, 2010)
Five priority programs were identified to help stabilize the economy and lay the groundwork for equitable growth. The government's priority with this core strategy is to enhance macroeconomic management, government operations, and effective fiscal management to promote domestic and international trade, make the Comorian economy more competitive, guarantee a low-cost energy supply, improve basic economic infrastructures and communication services, and finally to make investments to improve access to drinking water and a more healthy environment. The PEFA report prepared in 2008 entailed a comprehensive fiscal analysis.